Construction of BaTiO3/CeO2 heterojunction and comparative study on photocatalytic activity of degradation of different drugs - Ye, Chao; Li, Chengui (Frontiers in Materials, 2023)
A type II band aligned BaTiO3/CeO2 photocatalysts was constructed by a simple one-step solution synthesis method. The BaTiO3/CeO2 photocatalysts contain only cubic phase BaTiO3 and CeO2, and the particles are approximately spherical with a small amount of adhesion and agglomeration, and the average particle size is about 50 nm. TEM observation and element Mapping characterization confirmed the formation of special heterojunction between BaTiO3 and CeO2 and the presence of a large number of oxygen vacancies, which resulted in high visible optical absorption coefficient. The BaTiO3/CeO2 photocatalysts demonstrated high photocatalytic activity for the degradation of oxytetracycin hydrochloride and the optimal drug concentration, catalyst content and pH value are 50 mg/L, 1 g/L and 7, respectively. Simultaneously, the BaTiO3/CeO2 photocatalysts were selective for degradation of aureomycin hydrochloride, doxycycline hydrochloride and tetracycline hydrochloride. Other photocatalytic experiments show that the BaTiO3/CeO2 photocatalysts have high chemical and cyclic stability, and the synergistic effect of holes, hydroxyl radicals and superoxide radicals plays an important role in the whole photocatalytic process. This simple synthesis route provides a technical reference for constructing other wide-band gap semiconductors to respond to visible light.